Municipal solid waste management in Aba, Nigeria: Challenges and prospects - Ezechi, E.H. (Korean Society of Environmental Engineers, 2017)
Solid waste disposal and management is a critical problem in Nigeria. Annually, a huge quantity of municipal solid waste is generated in Aba. Municipal solid waste disposal in Aba poses severe challenge to environmental safety, public health and welfare of citizens. The situation is made worse by the indiscriminate dumping of refuse at roadsides, streets, waterways and empty lands. The impact of this waste management practice in Aba is environmental deterioration. Efforts to improve waste management in Aba have not recorded significant success. This paper therefore aims to highlight the challenges facing the waste management sector in Aba and proffer solutions on how to improve the sector. © 2017 Korean Society of Environmental Engineers.